The role of short-chain fatty acid on blood pressure regulation. Issue 5 (September 2016) - Miyamoto, Junki; Kasubuchi, Mayu; Nakajima, Akira; Irie, Junichiro; Itoh, Hiroshi; Kimura, Ikuo
Abstract : Purpose of review: The gut microbiota and its metabolites have been implicated in the regulation of host physiological functions such as inflammatory and metabolic responses. The short-chain fatty acid (SCFA) receptor is expressed in the kidney and blood vessels as well, and has been reported to function as a regulator of blood pressure (BP). This review highlights the role of SCFAs derived from gut microbial fermentation in the regulation of BP. Recent findings: Olfactory receptor 78 (Olfr78) is a member of the G-protein-coupled receptor family, and it plays a key role as a chemosensor in various tissues. Both Olfr78 and G protein-coupled receptor 41 (GPR41) are expressed in smooth muscle cells of blood vessels and they recognize SCFAs. Oral administration of SCFAs was found to change BP in vivo, an effect that was altered in Olfr78 and GPR41 -deficient mice. Summary: The regulation of BP via SCFA receptors has provided new insights into the interactions between the gut microbiota and BP control systems. We summarize these interactions and describe their contributions to a novel pathway involved in BP regulation. These recent findings could open new avenues for the development of therapeutic strategies for the treatment of cardiovascular diseases.